Qualities of Neurodynamic and Mental Functions of Athletes - Mykola Makarenko; Serhii Holiaka (Lesya Ukrainka Volyn National University, 2018)
Relevance. The research on the correlation between individual-typological qualities of higher nervous activity, sensomotor reaction, memory and attention functions and the achievements in sports could serve a scientific basis for carrying out theoretical and practical tasks for sports orientation and selection. The purpose of the research is to study the correlation between sports achievements and the qualities of neurodynamic and mental functions of athletes of various qualifications and orientations. The Results of the Work. It was found out that the qualities of the basic nervous processes correlated with the nature of athlete's sports activity. The highest indices to both functional lability and nervous processes force were observed in the groups of wrestlers and gymnasts, and the lowest indices were in the beginner's group. It was stated that the students with the best skills of the sensomotor reaction of various difficulty, memory and attention functions were those who had masters of sports or masters for sports. The analysis of the indices to the sensomotor reaction in groups of athletes in different sports revealed that the wrestlers were characterized by shorter latent periods of a simple visual-motor reaction while the fighters and representatives of game sports were characterized by complex visual-motor reactions. Due to regular trainings and competitions the athletes of high qualification keep necessary coordination, preserve and improve the level of correlation between different nervous processes that cause the increase in neurodynamic and mental functions. Taking into account the high determination of typological qualities of higher nervous system it is necessary to consider that the high level of the qualities in question of athletes of high qualification may be a result of natural selection that can be typical. Conclusions. Individual-typological qualities (functional mobility and basic nervous processes force) and the qualities of sensomotor reactivity together with individual mental functions constitute the neurophysiologic basis for the effectiveness of sports activity.